ANALISIS PENGARUH PERUBAHAN STATUS PEGAWAI KOMISI PEMBERANTASAN KORUPSI MENJADI APARATUR SIPIL NEGARA TERHADAP INDEPENDENSI KPK - Fajar Pravda Malik (2022)
This study aims to determine the independence of the Corruption Eradication Commission after experiencing a change in employment status from the previous status as an employee of the Corruption Eradication Commission to being an employee of the State Civil Apparatus. The existence of the Corruption Eradication Commission was initially considered to have extraordinary authority in terms of dealing with acts of corruption, until finally its authority and overall institutions underwent changes due to the revision of Law Number 19 of 2019 concerning the Corruption Eradication Commission. The concept used in making comparisons with similar state institutions in other legal systems is Independent Regulatory Agencies (IRA's), which in this concept emphasizes that an independent state institution can be said to be independent if it has three indicators: Institutional Independence, Functional Independence, Independence Personnel. This research refers to normative juridical which is a research that examines the study of document literature (Library Research). and The approach used by this research uses two approaches, namely the statutory approach and the comparative approach.